Unbounded boundaries and shifting baselines: Estuaries and coastal seas in a rapidly changing world. (5th November 2017) - Little, S.; Spencer, K.L.; Schuttelaars, H.M.; Millward, G.E.; Elliott, M.
Abstract: This Special Issue of Estuarine, Coastal and Shelf Science presents contributions from ECSA 55; an international symposium organised by the Estuarine and Coastal Sciences Association (ECSA) and Elsevier on the broad theme of estuaries and coastal seas in times of intense change. The objectives of the SI are to synthesise, hypothesise and illustrate the impacts of global change on estuaries and coastal seas through learning lessons from the past, discussing the current and forecasting for the future. It is highlighted here that establishing impacts and assigning cause to the many pressures of global change is and will continue to be a formidable challenge in estuaries and coastal seas, due in part to: (1) their complexity and unbounded nature; (2) difficulties distinguishing between human-induced changes and natural variations and; (3) multiple pressures and effects. The contributing authors have explored a number of these issues over a range of disciplines. The complexity and connectivity of estuaries and coastal seas have been investigated through studies of physicochemical and ecological components, whilst the human imprint on the environment has been identified through a series of predictive, contemporary, historical and palaeo approaches. The impact of human activities has been shown to occur over a range of spatial and temporal scales, requiring the development of integrated management approaches. These 30 articles provide an important contribution to our understanding and assessment of the impacts of global change. The authors highlight methods for essential management/mitigation of the consequences of global change and provide a set of directions, ideas and observations for future work. These include the need to consider: (1) the cumulative, synergistic and antagonistic effects of multiple pressures; (2) the importance of unbounded boundaries and connectivity across the aquatic continuum; (3) the value of combining cross-disciplinary palaeo, contemporary and future modelling studies and; (4) the importance of shifting baselines on ecosystem functioning and the future provision of ecosystem services.